2013
DOI: 10.1097/01.ehx.0000425919.49371.ec
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspartame on the pituitary thyroid axis of adult male albino rat and the possible protective effect of Pimpinella anisum oil

Abstract: BackgroundAspartame is a synthetic sweetener. Its metabolites can be toxic to many organs such as liver and kidney. Pimpinella anisum (P. anisum) has been used for different purposes as an antioxidant, hepatoprotective, and anti-inflammatory agent. AimThe present work was carried out to study the histological changes in the pituitary thyroid axis of adult male albino rats after aspartame treatment and the possible role of P. anisum in minimizing these changes. Materials and methodsTwenty-five adult male Albino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…It was found that anise could have a radical scavenging effect, inhibiting H 2 O 2 -chelating, and Fe 2+ -chelating activity by more than 70% [38]. Similar results were observed by El Haliem [22] who reported that the prolonged consumption of ASPinduced disturbance in the pituitary thyroid axis, where the use of P. anisum decreased the toxic effect of ASP.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It was found that anise could have a radical scavenging effect, inhibiting H 2 O 2 -chelating, and Fe 2+ -chelating activity by more than 70% [38]. Similar results were observed by El Haliem [22] who reported that the prolonged consumption of ASPinduced disturbance in the pituitary thyroid axis, where the use of P. anisum decreased the toxic effect of ASP.…”
Section: Discussionsupporting
confidence: 66%
“…Chemical studies have demonstrated that the aniseed contains anethole (85%) as an active ingredient, in addition to eugenol, methylchavicol, anisaldehyde, and estragole [21]. Pimpinella anisum has been used for different purposes as an antioxidant, hepatoprotective, antiinflammatory agent, and toxicity of the pituitary thyroid axis [22]. Pimpinella anisum may have therapeutic effects in diseases such as digestive, gynacologic, neurologic, and respiratory disorders [23].…”
Section: Introductionmentioning
confidence: 99%
“…The anisum oil have a great radical chelating role through inhibiting Fe2+-chelating and H2O2-chelating activity up to 70% 25 . These results were observed also by El Haliem 26 who decided that long term use of ASP made alterations in the axis between pituitary and thyroid glands, but anisum oil lower bad effect that caused by long term use of ASP.…”
Section: Discussionsupporting
confidence: 54%
“…Reactive oxygen species (ROS) cause DNA damage by speeding up cell death and lowering sperm cell counts, both of which are indications of male infertility (25).ROS attack polyunsaturated fatty acids on sperm membranes, causing remodeling of the biophysical properties and composition of the sperm membranes by altering their electron stability, membrane potential, and energy production capacity, which affects the production of reproductive hormones by the testes and ovaries (26). El-Haliem (27) found that ASP treatment causes enlargement of most cells in the pars distalis and causes histological alterations in the pituitary-thyroid axis in adult male albino rats, as well as reduced pituitary hormone production. Additionally, Puica et al (28) found that prolonged treatment of ASP to white Wistar rats at the pre-pubertal stage caused neurodegenerative consequences, particularly in the hypothalamus, as well as significant structural and functional changes in the hypothalamic-pituitary axis.…”
mentioning
confidence: 99%